Why Shouldn’t Rural Kids Have It All? Place-conscious Leadership in an Era of Extralocal Reform Policy - Budge, Kathleen M. (Education Policy Analysis Archives, 2010)
This article explores school and community leaders' beliefs about standards-based reform and the purposes of local schooling in a single rural community in the western United States. The study used interviews of 11 community and school leaders in the community. Participants engage in a balancing act between serving local interests and satisfying extralocal mandates. They care about both the students they serve and the place they inhabit, and their own assessment of the educational enterprise indicated that state and federal policy had had little constructive influence on either. The conclusion explores critical place-consciousness as a possible tool to refocus rural educators' attention on the intent of the standards-based movement and to ensure that schooling supports individual student success and the needs of rural communities.